Bridging the Digital Divide in Rural Peru: A Mixed-Methods Analysis of Educational Technology Access, Infrastructure Barriers, and Teacher Preparedness in Andean Communities - Antonio, Romero-Flores Robert; Yosef, Gomez-Quispe Hugo; Aparicio, Castillo-Suaquita Fredy; Yasmín, Flores-Cano Yusey del Pilar; Wilson, Mamani-Rodrigo; Wildo, Sucasaire-Monroy; Javier, Calli-Olvea; Alfredo, Ccari-Sucasaca (Journal of Posthumanism, 2025)
Digital education access encounters considerable obstacles in Peru, where technological, social, and geographical issues restrict internet connectivity and educational prospects. The World Bank reports that Peru ranks poorly compared to other Latin American nations in terms of internet bandwidth. In remote areas, children may trek up to three hours to reach in-person classes, while in urban centers like Puno and Juliaca, universities have provided subsidized internet access for students during COVID-19 due to families' limited financial means. This study explores the pandemic's impact on poverty and educational internet access in Peru. Our research indicates that schoolteachers exhibit low levels of ICT competency, yet the Ministry of Education does not offer evaluation or training programs for technology integration. We analyze a case study of an Andean school and assess state initiatives aimed at enhancing internet connectivity infrastructure. The results underscore the ongoing digital divide that hampers educational equity in Peru.